Synthesis and Evaluation of Cytotoxic Activity of RuCp(II) Complexes Bearing (Iso)nicotinic Acid Based Ligands - Bárbara Marques; Diogo M. Engrácia; João Franco Machado; Jaime A. S. Coelho; Filipa Mendes; Tânia S. Morais (Pharmaceuticals)
Background/Objectives: Cancer remains one of the major challenges of our century. Organometallic ruthenium complexes are gaining recognition as a highly promising group of compounds in the development of cancer treatments. Methods: Building on the auspicious results obtained for [Ru(η5-C5H5)(PPh3)(bipy)][CF3SO3] (TM34), our focus has shifted to examining the effects of incorporating bioactive ligands into the TM34 framework, particularly within the cyclopentadienyl ring. Results: In this study, we report the synthesis and characterization of two new ruthenium(II) complexes with the general formula [Ru(η5-C5H4CCH3=R)(PPh3)(bipy)][CF3SO3], where R represents a nicotinic acid derivative (NNHCO(py-3-yl)) (1) or an isoniazid derivative (NNHCO(py-4-yl)) (2). The complexes were fully characterized using a combination of spectroscopic techniques and computational analysis, revealing the presence of E/Z-hydrazone isomerism. Stability studies confirmed the robustness of both complexes in biological media, with compound 1 maintaining good stability in buffer solutions mimicking physiological (pH 7.4) and tumor-like (pH 6.8) environments. The cytotoxicity of the complexes was evaluated in vitro in several human cancer cell lines, namely melanoma (A375), alveolar adenocarcinoma (A549), epidermoid carcinoma (A431), and breast cancer (MDA-MB 231). Conclusions: Both compounds exhibited moderate to high cytotoxic activity, with complex 1 showing a greater propensity to induce cell death, particularly in the A431 and MDA-MB 231 cell lines.